2010
DOI: 10.1080/02640414.2010.484067
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defence and inflammatory response in professional road cyclists during a 4-day competition

Abstract: Cycling competitions represent an important physical overload even for well-trained individuals. In six professional cyclists, we studied the adaptive oxidative and anti-inflammatory response to a 4-day road cycling competition and its relationship with melatonin, an antioxidant and anti-inflammatory stress hormone. Blood and urine samples were collected before and after the competition. Plasma lipid peroxidation, cytokines (interleukin-1beta, interleukin-6, and tumour necrosis factor-alpha), creatine kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
3
17
0
4
Order By: Relevance
“…The seven cycling studies including markers of lipid peroxidation (MDA) and determination of reactive oxygen metabolites (d-ROMS) showed a consistent effect for increases in lipid peroxidation post-race, with relative increases of between 8 and 144 % [113][114][115][116][117][118][119]. The largest increase in MDA of 144 % was following a single stage race of 229 km [115], with MDA increases of 23-69 % recorded after a single mountain stage race of *171 km [117,120], in contrast to no significant change (*9 %) following a flat stage of *166 km [119].…”
Section: Evidence For Alterations In Redox Homeostasis (Arh) Followinmentioning
confidence: 95%
See 1 more Smart Citation
“…The seven cycling studies including markers of lipid peroxidation (MDA) and determination of reactive oxygen metabolites (d-ROMS) showed a consistent effect for increases in lipid peroxidation post-race, with relative increases of between 8 and 144 % [113][114][115][116][117][118][119]. The largest increase in MDA of 144 % was following a single stage race of 229 km [115], with MDA increases of 23-69 % recorded after a single mountain stage race of *171 km [117,120], in contrast to no significant change (*9 %) following a flat stage of *166 km [119].…”
Section: Evidence For Alterations In Redox Homeostasis (Arh) Followinmentioning
confidence: 95%
“…Antioxidant enzymes were measured in seven procycling studies, of which three studies measured enzymatic activity in lymphocytes [114,117,118], two studies in neutrophils [119,122] and four studies in RBCs [28,115,116,122]. In the professional cyclists, racing either a 171 km mountain stage, or two flat stages of 164.5 and 166.3 km, increased activity of the lymphocyte antioxidant enzymes for SOD (91 %), GPx (87 %), CAT (21 %) and Gr (61 %) [114,118], and in contrast, neutrophil antioxidant enzymatic activity for CAT (40-51 %), SOD (38-47 %) and GPx (10-37 %) decreased after a 171 km mountain stage [117,122] and a flat stage of *166 km [119].…”
Section: Than Inmentioning
confidence: 99%
“…By contrast, strenuous exercise of long duration and exhaustive sprint training may overwhelm the body's capacity to detoxify reactive oxygen and nitrogen species from the body. It is now clear that oxidative stress, muscle damage, and inflammation are associated events during exercise of high intensity (Serrano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Strenuous exercise represents a physical stress that challenges homeostasis, and, therefore, it may lead to an increased production of ROS or suppression of the antioxidant levels [20,60]. It has been confirmed that extreme endurance, such as ironman triathlons and longdistance running events, increase OS indeed [60][61][62]. While physiological levels of ROS are necessary for normal sperm functionality (maturation, capacitation, hyperactivation, acrosome reaction, and sperm-oocyte fusion), pathological levels may cause lipid peroxidation, DNA damage, and ultimately lead to sperm death [63].…”
Section: Exercise and The Oxidative Stress Systemmentioning
confidence: 99%